Test your aptitude and ability - "Lewis, Gareth" (Delhi, 2000)
awing on the latest research and trends, this text is part of a series which aims to enhance readers' understanding of the key topics in management skills and competence. This text focuses on aptitude and ability testing, providing a framework against which to evaluate your own performance.
Keywords: "Management, Aptitude and ability skills"